Measuring Pavement Permanent Deformation in Accelerated Pavement Testing. Issue 5 (May 2020) - Xue, Wenjing; Flintsch, Gerardo W.; Diefenderfer, Brian K.
Permanent deformation is an essential criterion for evaluating pavement performance. In an accelerated pavement testing (APT) experiment at the Virginia Tech Transportation Institute, a laser profiler, multi-depth deflectometer (MDD), and forensic investigation were used to measure the permanent deformation of a pavement system. This paper analyzes the permanent deformation measured via the three methods during the APT experiment. The major concern among the three methods is applicability rather than accuracy. To measure surface deformation, the laser profiler is a more practical method than MDD in APT, as it can scan the whole surface instead of just one point. To measure the deformation within a pavement structure, MDD provides deformation development throughout the whole experiment, which is helpful for a deeper understanding of pavement materials and structures. However, MDD is also more expensive and requires significant installation effort and maintenance during the experiment compared with forensic investigation, which also needs to be considered.